Munster and Minjung : re-reading the Anabaptist Münster kingdom from a perspective of Korean Minjung (common people) theology - Chung, Youjin (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.